KAJIAN HUKUM MENGENAI RENVOI YANG BARU DILAKUKAN SETELAH DIKELUARKAN SALINAN AKTA - DEBORAH DEBORAH (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Edy Ikhsan3. Rudy Haposan A Notary has to perform his right and obligation as a Notary Officials by issuing deeds and serving people. In practice, a Notary is demanded to be professional and cautious in issuing authentic deeds. This research focuses on Notary’s cautiousness in issuing authentic deeds such as typographical error. One of the efforts that can be made by a Notary is renvoi (removal) as stated in the Notarial Act. Renvoi that is done by neglecting the provisions stipulated in the constitution of Notarial Act will have a legal consequence to the concerned Notary. It can also be found in the copy of deeds; thus, this research further studies the provisions regulating renvoi pursuant to the Notarial Act, the efforts that can be made by a Notary after the copy of the deed is issued and the legal protection of the renvoi which is done by the time a deed has already been issued.Keywords: Renvoi, Deed, Copy of Deed